KATA SEPAKAT DALAM PERJANJIAN DAN RELEVANSINYA SEBAGAI UPAYA PENCEGAHAN WANPRESTASI - Isdian Anggraeny; Sholahuddin Al-Fatih (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
In a juridical-formal, firmly determined, that each agreement requires the agreement of the parties. However, the implementation of normative tools is not as easy as the textual sounds. Through a juridical approach, writing with the theme "Agree to the Agreement and its Relevance as a Prevention of Default", raised two interesting problems. First, how is the relevance of the agreement in the agreement as an effort to prevent default; Second, what is the ideal format for agreement in an agreement. The findings in this study confirm, that: First, the agreement is the key word in ensuring the implementation and fulfillment of the promises of the parties to the agreement. Therefore, in agreement in general, the agreement has relevance to prevent defaults. Second, ideally, in every agreement it is necessary to ensure that the parties truly understand what has been agreed both formally and materially (substantially).